Frustrated tunnelling ionization during strong-field fragmentation of D3+ - McKenna, J.; Sayler, A. M.; Gaire, B.; Kling, Nora G.; Esry, Brett D.; Carnes, K. D.; Ben-Itzhak, Itzik (My University, 2013)
We reveal surprisingly high kinetic energy release in the intense-field fragmentation of D[subscript 3][superscript +] to D[superscript +] + D[superscript +] + D with 10[superscript 16]Wcm[superscript −2], 790 nm, 40 fs (and 7 fs) laser pulses. This feature strongly mimics the behaviour of the D[superscript +] + D[superscript +] + D[superscript +] channel. From the experimental evidence, we conclude that the origin of the feature is due to frustrated tunnelling ionization, the first observation of this mechanism in a polyatomic system. Furthermore, we unravel evidence of frustrated tunnelling ionization in dissociation, both two-body breakup to D + D[subscript 2][superscript +] and D[superscript +] + D[subscript 2], and three-body breakup to D[superscript +] + D + D.
Keywords: D[subscript 3][superscript +]; Frustrated tunnelling ionization; D3+